2011
DOI: 10.4271/2011-37-0015
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation into the Wake Structure of Square Back Vehicles and the Effect of Structure Modification on Resultant Vehicle Forces

Abstract: Citation: LITTLEWOOD, R., PASSMORE, M.A. and WOOD, D., 2011. An investigation into the wake structure of square back vehicles and the effect of structure modification on resultant vehicle forces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 11 publications
1
24
0
Order By: Relevance
“…A quarter scale Windsor Model, Figure 1, as used in [4,7,8,14,15] was used for this work. The model is constructed of a machinable model board and gives a blockage ratio of 4.4% in the 2.5m 2 working section.…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…A quarter scale Windsor Model, Figure 1, as used in [4,7,8,14,15] was used for this work. The model is constructed of a machinable model board and gives a blockage ratio of 4.4% in the 2.5m 2 working section.…”
Section: Modelmentioning
confidence: 99%
“…The use of two component, two dimensional PIV is well documented in a variety of situations [4,7,8,9,10] and traditionally involves a single camera that is normal to the measurement plane, a pulsed laser passing through a plano-concave lens to create a diverging sheet of light focused to a thickness of around 1mm, neutrally buoyant seeding particles (such as DEHS solution which has been atomized to form 1μm particles) and a computer containing a timing board that allows for the control of the system. This technique is particularly accurate when there is only a small amount of through plane motion so that the majority of the particles captured by the camera in the double frame image pair remain within the light sheet.…”
Section: Introductionmentioning
confidence: 99%
“…In a separate study Littlewood, Passmore & Wood [14] considered the application of horizontal slats to the base of a squareback geometry, with the intention of disrupting the near wall flow and modifying the wake structure. At model scale this produced a drag reduction of up to ∆C D =0.008 and was consistent with changes to the measured base pressures.…”
Section: Introductionmentioning
confidence: 99%
“…It was assumed having seen work from Littlewood [12], that the flow over the base plate was symmetrical. In total the base plate contains 79 tappings, with 15 tappings distributed around the centreline of the model.…”
Section: Pressure Measurementsmentioning
confidence: 99%
“…Passive flow control techniques that have been applied recently are demonstrated in work by Littlewood [4] and others [5][6][7][8][9][10][11] where the work has proved the vast scope for base pressure increase that has yet to be fully exploited. However most of this work has been conducted with models with smooth floor, yet it has been found that pressure recovery found on the simplified model geometry does not cross over to full scale testing, as shown by Littlewood [12].…”
Section: Introductionmentioning
confidence: 99%